Course-Based Undergraduate Research Experiences (CUREs) in STEM Higher Education: Global Trends, Benefits, and Prospects for Indonesian Physics Education - Arifa, Aulia; Suharno; Harjunowibowo, Dewanto (Proceeding of International Joint Conference on UNESA, 2025)
Course-based undergraduate research experience (CURE) is widely recognized as a transformative approach to advancing STEM education. However, their integration into physics, especially in Indonesian higher education, remains limited. This article presents a comprehensive bibliometric analysis of 500 Scopus-indexed CURE publications from 2015 to 2025. The analysis conducted with Excel for data filtering and visualizing with VOSviewer highlights trends, disciplinary disparities, and the unique potential of CUREs in physics. The study identifies critical challenges and opportunities in adopting CUREs in physics labs and curricula and draws comparisons with more established fields, such as the life sciences and chemistry. To contextualize the global findings from bibliometrics analysis, a quantitative survey with Likert scale scoring and open-ended questions was conducted with second-year physics education students at Universitas Sebelas Maret. The survey result reveals their strong enthusiasm and readiness for authentic, research-based learning, underscoring the relevance of integrating CUREs into Indonesia’s STEM curriculum and educational priorities. The findings articulate the key benefits of CUREs, including enhancement of scientific identity, critical thinking, and research skills, while also outlining practical implementation strategies, such as curriculum design, faculty preparation, and scalable, low-cost research experiences. This article advocates for broader CURE adoption in Indonesian physics education to prepare students for the evolving demands of the modern workforce.